Response Surface Optimization for Extraction of Phenolics from Coconut Testa (Pairings) - Gunathilake, K. D. P. P.; Dharmawansa, K. V. S. P.; Weerasinghe, K. A. U. D.; Gimasha, A. J. N. (International Coconut Community, 2018)
Response surface methodology in conjunction with central composite design (CCD) was performed in the present study to optimize the extraction parameters for assessing maximum yield of total phenolic content and antioxidant capacity from coconut pairings. Solvent concentration (30-100%), extraction temperature (30-60°C) and extraction time (30-90 min) were used as the independent variables. The optimum conditions for extraction of total phenolics and antioxidant capacity from coconut pairings were found to be at ethanol concentration, 47.75% (v/v); extraction temperature, 49.84°C; and extraction time, 68.66 minutes. Under these optimal conditions, the model predicted a maximum response of 18.97 mg GAE/ g DW total phenolics and 38.09 mg AAE/g DW total antioxidant capacity of coconut pairing extracts and they were in close agreement with predicted values, thus indicating the suitability of the models developed and the success of RSM in optimizing the extraction conditions.